The modulation of microglia by astrocytes : a role for CD200 - Cox, Fionnuala (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Glial cell activation is believed to play a critical role in the pathogenesis of neurodegenerative diseases, impairing neuronal function and ultimately leading to cognitive decline. Epidemiological studies have advocated the benefit of anti-inflammatory drugs in decreasing the risk of developing, or delaying the onset of, dementia. The objective of this thesis was to investigate the consequences of modulating glial cell activity with two different compounds, FGL and a CD200 fusion protein. First, the ability of the NCAM-mimetic peptide, FGL, to attenuate LPS and Aβ- stimulated changes on primary mixed glial cells and isolated microglia was investigated. Next, the dependence of the action of FGL on expression of the immunosuppressive molecule CD200 was examined, using glia prepared from wildtype and CD200-/- animals. Finally, the modulatory effects of CD200Fc on LPS- and aged-induced deficits in LTP and in markers of inflammation in hippocampus were explored.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin